2012
DOI: 10.2478/s11536-011-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in a developing country — how much patients know about disease

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…When compared to a similar study from 2012 [8], hospitalized patients in this study demonstrated better knowledge about TB. One possible reason for this could be that hospital patients were able to obtain information about various respiratory diseases, including TB, quickly after admission using the internet and mass media, which are more accessible nowadays than in previous years.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…When compared to a similar study from 2012 [8], hospitalized patients in this study demonstrated better knowledge about TB. One possible reason for this could be that hospital patients were able to obtain information about various respiratory diseases, including TB, quickly after admission using the internet and mass media, which are more accessible nowadays than in previous years.…”
Section: Discussioncontrasting
confidence: 40%
“…The patients were asked to complete a questionnaire designed specifically for this study by the authors (Supplementary File 1). A similar questionnaire was used in 2012 for a study on TB patients conducted by the first author [8]. Outpatients (ambulatory, AMB) were surveyed in the IPDV's polyclinic service, while hospitalized patients (HOS) were surveyed in the IPDV's hospital facilities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of TB is more easily affected by social and economic factors than any other disease [5]. In addition to HIV infection, malnutrition, increased susceptibility of infants and the elderly, and poverty [1,6,7], a lack of awareness about TB is also considered to be an essential factor that increases the risk of exposure to TB [8].…”
Section: Introductionmentioning
confidence: 99%